ANALISIS PENDAPATAN DAN KONSUMSI MASYARAKAT PESISIR PANTAI (Studi Kasus: Di Dusun Rarumis Desa Karor Kecamatan Lembean Timur) - Mianty ., Pangerapan; O. Esry. H. Laoh; Ellen G. Tangkere (AGRI-SOSIOEKONOMI, 2018)
The study aims to determine the income and consumption of coastal communities in Rarumis hamlet eastern sub-district of Lembean. The data used are primary data and secondarydata. Primary data were obtained by using direct interview of technique on respondents by using questionnaire (questionnaire). While secondary data is obtained from Karor village office ofeastern sub-district of Lembean. Sample method in this study used population method where sampling or data taken as a whole. The concept of meansurement of variables used in householdconsumption and income levels. The result of this research shows that Hamlet Rarumis Districts of eastern daienan there are two income from society that is basic income as farmer obtained byresult of plant of chili, corn, coconut and side income as farm laborer working in owned land of others, as fisherman doing fish at sea for sale in other villages, as well as small businesses by opening stalls. Income that the perolwh community is used to meet the consumption of each family through the expenditure of primary, secondary and tertiary needs.